The Implementation of the Cambridge Lower Secondary English Curriculum: Teachers’ Voices at One Private School in Palembang - Muhamad Holandyah; Dian Erlina; Lenny Marzulina; Diah Yulianti (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
The Cambridge curriculum is one of the international curricula. In Indonesia, Cambridge curriculum has been implemented, especially for teaching English. This study was aimed at finding out English teachers' perceptions toward the implementation of the Cambridge Lower Secondary English Curriculum at one private school in Palembang, Indonesia. A qualitative design with a case study was employed for this study. The data were gathered through in-depth interviews with two English teachers. Thematic analysis was used to analyze the research data. The results of the study revealed the three stages of implementing the curriculum: (1) program development, (2) implementation of learning, and (3) evaluation.